A Sikh Perspective on Life-Stress: Implications for Counselling - Sandhu, Jaswinder Singh (Canadian Journal of Counselling and Psychotherapy, 2007)
This paper presents the Sikh life-stress model as a culture-specific intervention. The paper looks at the Sikh world-view, from which it delineates the Sikh perspective on life-stress. It further outlines a framework for incorporating the Sikh life-stress model into the Western counselling context, and concludes with a case vignette to demonstrate how the life-stress model can be integrated with conventional counselling approaches.